Pemberdayaan Masyarakat Dalam Mendukung Kinerja Bidang Kewilayahan Pemerintahan Desa Brondong, Lamongan - Fakihardi, Fatan; Rizky Tri Demarwan; Indah Azhari; Nabila Senja Wahyuningtias (Health Community Engagement, 2023)
Brondong Village is one of 19 villages in the Subdistrict of Sumbang. The development and independence of a village depend on the productivity of the individual and village government organizations. Based on the results of an interview with one of the governments of the village, Mr Nasrul, he conveyed several problems, one of which was that around 50% of the village population of productive age did not have adequate soft skills. Another problem is that from the work of village government, soft skills are needed that can ease the work in the form of village spatial planning and design as well as village social maps. The solution offered to overcome partner problems is to provide 3D design training using Sketch Up to support the performance of the Regional Government of Brondong Village, Lamongan District. The method used is to provide 3D training using Sketch Up and evaluated using a questionnaire to determine the level of understanding of the participants. This activity lasted for two days by providing basic drawing materials on the first day and making 3D designs on the second day using Sketch Up software. The result of this training is a simple 3D house design made by the participants. The level of satisfaction of the training participants reached 70% at the level of satisfied, 20% at the level of very satisfied and 10% neutral. Participants who have received the knowledge of 3D design training using Sketch Up are expected to be able to develop their skills to design village physical infrastructure.